2018
DOI: 10.11158/saa.23.9.6
|View full text |Cite
|
Sign up to set email alerts
|

<span style="font-family: Times New Roman;">Does size matter? Fecundity and longevity of spider mites (Tetranychus urticae) in relation to mating and food availability</span>

Abstract: Bigger animals tend to live longer than the small ones across species, but whether body size also has a robust relationship with survival within species remains to be determined. Here, the association between body size and fitness traits was examined through two food treatments (starvation and fed ad libitum) for both virgin and mated spider mites, Tetranychus urticae. The longevity of spider mites differed significantly across treatments, with feeding ad libitum increasing the survival of both males and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
(53 reference statements)
0
18
0
Order By: Relevance
“…The sample sizes ranged 31-41 pairs in each treatment. The experimental arenas and setup were the same as in Li and Zhang (2018) and the mites were kept under standard laboratory conditions at 25 ± 2 °C, 70% ± 10% humidity, 16 : 8 h light : dark cycle.…”
Section: General Experimental Protocolmentioning
confidence: 99%
“…The sample sizes ranged 31-41 pairs in each treatment. The experimental arenas and setup were the same as in Li and Zhang (2018) and the mites were kept under standard laboratory conditions at 25 ± 2 °C, 70% ± 10% humidity, 16 : 8 h light : dark cycle.…”
Section: General Experimental Protocolmentioning
confidence: 99%
“…We included both males and females as subjects, aiming to examine the sex difference in aging by exposing them to three treatments of IF with controls fed ad libitum. Our previous study found that bigger females have higher starvation resistance than small males [36]. Therefore, we expected that the effects of IF would be level and sex dependent, and the longevity and reproduction of males and females would differ across the treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Guarding spider mite males are mainly attracted (arrested) by pheromones released by T-females [35,36]. Body size can play a role in male-male competition, with larger males usually winning fights over smaller ones [15], and male choice because of a positive correlation between female body size and fecundity [32]. In our experiments, body size differed neither between males nor between T-females from the Y-and G-populations.…”
Section: Proximate Mechanismsmentioning
confidence: 48%
“…In the laboratory, both populations were separately kept on detached primary leaves of common bean, Phaseolus vulgaris, resting on water-saturated cotton pads inside Styrofoam trays. Assuming a generation time of about 12 to 15 days [32], the Yand G-populations had been subjected to closed rearing for >120 and >50 generations, respectively, before conducting the experiments. Multi-generational closed rearing and haplodiploidy (arrhenotoky) allowed considering individuals from the same population as kin and from different populations as non-kin.…”
Section: Experimental Animalsmentioning
confidence: 99%